2016
DOI: 10.1088/1742-5468/2016/04/043202
|View full text |Cite
|
Sign up to set email alerts
|

Critical properties of the contact process on a scale-free homophilic network

Abstract: . Using the contact process model within a Monte Carlo numerical simulation approach, we mimic an epidemic spreading on a homophilic network, a scale-free network displaying a small world effect, to show a continuous phase transition to an absorbing-state at a critical threshold . Since the connection number k of the vertices’ homophilic network is cumulative, the degree distribution exhibits, for a large value of networks, a power-law behavior according to , with the distribution exponent . A finite-size scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Numerical simulations in regular networks have shown that the phase transition between active and inactive regimes belongs to the directed percolation universality class [10] . A previous study of the contact process (CP) model on the homophilic network unveiled that the numerical values of the critical exponents, obtained from the heterogeneous mean-field theory and from a standard scale-free network model, were different from those found on the homophilic one [11] .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerical simulations in regular networks have shown that the phase transition between active and inactive regimes belongs to the directed percolation universality class [10] . A previous study of the contact process (CP) model on the homophilic network unveiled that the numerical values of the critical exponents, obtained from the heterogeneous mean-field theory and from a standard scale-free network model, were different from those found on the homophilic one [11] .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, more attention has been devoted to the study of social [22] , cultural phenomena and the spread of viruses on computers [23] , and epidemic diseases [19] , [20] in complex networks. Recently, the CP and SIS models were shown to share the same universality class in the deterministic Apollonian network [11] , [19] , [20] , while the former model in the homophilic network exhibited a phase transition [11] . Pastor-Satorras [12] , [13] showed that there was no phase transition in the SIS model in a random scale-free network model.…”
Section: Introductionmentioning
confidence: 99%
“…The Contact Process (CP) model [12][13][14][15], Diffusive Epidemic Process (DEP) model [16][17][18][19][20], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Investigouse o modelo suscetível-infectado-suscetível (SIS) por diferentes ângulos, por exemplo, comparou-se resultados teóricos e de simulações numéricas [70], fez-se investigações em redes aleatórias livres de escalas [71]. O processo de contato (que equivale ao SIS em redes regulares) também foi estudado de diversas formas, por exemplo, investigou-se o comportamento crítico em redes do tipo "small world" [72], em junções tipo estrela [73] e em uma rede livre escala de homofílica [74]. Redes complexas também foram utilizadas para representar metapopulações [75] no estudo dos efeitos de estruturas de populações locais.…”
Section: Populações Biológicas E a Mecânica Estatística De Não-equilíunclassified
“…74) em que = λ − λ c e f , g e j são funções universais. Das leis de escalas notamos que podemos utilizar o cruzamento da grandeza u para determinar o ponto 5.3.…”
unclassified